Emerging Imaging and Sensing Technologies for Security and Defence VI 2021
DOI: 10.1117/12.2602089
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz-to-infrared converter based on the polyvinylchloride matrix with embedded gold nanoparticles

Abstract: Prospects for the development of devices for visualizing terahertz (THz) radiation sources can be associated with the use of the results of old studies (1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978) on the absorption of THz radiation by metal nanoparticles. This "renaissance" demonstrates that metallic nanoparticles can be used as nanotransducers of invisible THz radiation to infrared (IR) radiation detectable by a commercial IR camera. The investigated THz-to-IR converter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…-The NP's size D is smaller than the penetration depth d of EM radiation with the frequency ν: D ≤ d. -The phonon wavelength λ at the frequency of the incident EM radiation ν is not larger than the NP's size D: λ ≤ D ≤ d. -The Heisenberg relation for the momenta of a phonon and an electron in an NP of size D ensures the fulfillment of the law of conservation of momentum upon excitation of a phonon. -The GNP's size D should not be smaller than the size, in which spontaneous emission of THz radiation by a (small enough) GNP begins, i.e., D > 8 nm, 58 in order to prevent the GNP's cooling via emission of THz photons. This observation was guided by our study 58 dedicated to a suggested explanation of the size effect in the heterogeneous catalysis on GNPs (see also Appendix A in this paper).…”
Section: Heating Of Metal Nps By Thz Radiationmentioning
confidence: 99%
See 4 more Smart Citations
“…-The NP's size D is smaller than the penetration depth d of EM radiation with the frequency ν: D ≤ d. -The phonon wavelength λ at the frequency of the incident EM radiation ν is not larger than the NP's size D: λ ≤ D ≤ d. -The Heisenberg relation for the momenta of a phonon and an electron in an NP of size D ensures the fulfillment of the law of conservation of momentum upon excitation of a phonon. -The GNP's size D should not be smaller than the size, in which spontaneous emission of THz radiation by a (small enough) GNP begins, i.e., D > 8 nm, 58 in order to prevent the GNP's cooling via emission of THz photons. This observation was guided by our study 58 dedicated to a suggested explanation of the size effect in the heterogeneous catalysis on GNPs (see also Appendix A in this paper).…”
Section: Heating Of Metal Nps By Thz Radiationmentioning
confidence: 99%
“…This article is based on a modified and expanded version of the SPIE Proceedings paper "Terahertz-to-infrared converter based on the polyvinylchloride matrix with embedded gold nanoparticles." 9…”
Section: Disclosuresmentioning
confidence: 99%
See 3 more Smart Citations